2018
DOI: 10.1155/2018/5956301
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing a Client-Centred Practice with the Canadian Occupational Performance Measure

Abstract: Background The active participation of clients is an important aspect of rehabilitation quality as conceptualized in client-centred practice (CCP). A recommended outcome measure for enhancing CCP is the Canadian Occupational Performance Measure (COPM). However, the relationship between COPM use and CCP enhancement has not been documented. Aim The aim of this study was to examine whether the use of the COPM enhanced CCP. Methods We performed a scoping review in five steps: (1) identifying a search strategy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 40 publications
0
39
0
1
Order By: Relevance
“…This high usability of the COPM with cognitive impairment diagnoses emphasizes the importance of active participation of clients in formulating their own goals to international occupational therapy practice. A scoping review concluded that the use of the COPM can enhance client-centered practice by improving awareness of the client's goals for the future, thereby reinforcing a partnership with a collaborative goal setting [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This high usability of the COPM with cognitive impairment diagnoses emphasizes the importance of active participation of clients in formulating their own goals to international occupational therapy practice. A scoping review concluded that the use of the COPM can enhance client-centered practice by improving awareness of the client's goals for the future, thereby reinforcing a partnership with a collaborative goal setting [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This measure determines occupational preferences and priorities; and evaluates the perceived OP and satisfaction while performing the occupation [ 34 ]. The individuals were asked to state OP problems and concerns in three performance areas; self-care, productivity and leisure activities [ 35 ]. The importance of activities were ranked between 1 and 10 (1: not important, 10: very important), and then the top five were graded in terms of performance and satisfaction levels.…”
Section: Methodsmentioning
confidence: 99%
“…Normalizing influences may in part explain findings that students with higher implicit fat bias currently align themselves with frames of references that focus more at client factors with associated diagnostic and procedural clinical reasoning focused upon improving individual function. In fact, previous research suggests that therapists who align themselves more within a medical paradigm due to practice contexts tend to prefer biomedical or rehabilitative FOR versus occupation-based intervention approaches (Enemark Larsen, Rasmussen, & Christensen, 2018;Rosewilliam, Sintler, Pandyan, Skelton, & Roskell, 2016). These findings suggest occupational therapists should question interventions with the fat community and the contextual influences of clinical encounters that focus primarily on weight reduction as previous research suggests this focus acts as a barrier to participation (Drury & Louis, 2002) countering professional principles of client care (American Occupational Therapy Association, 2015a).…”
Section: Discussionmentioning
confidence: 99%